ENVİRONMENTAL MANAGEMENT AND INTERNAL MARKETİNG – EXAMPLE OF DOMESTİC AİRLİNE EMPLOYEES (Third Sector Social Economic Review, 2023)
In today's world, where there is increasing demand and decreasing resources, environmental management, which is used for the effective use of resources, takes the lead in both quality and sustainability practices of organizations. In the study, the effects of environmental management and internal marketing perception in domestic airline companies in the Turkish civil aviation sector were researched, and the interaction of the sub-dimensions of the related concepts was emphasized. Environmental management scale and internal marketing scales were used in the study. The data obtained from 406 employees working in domestic airline companies in Turkey were analyzed using SPSS 26.0 and AMOS statistical programs. The statistical results show a significant correlation between internal marketing practices and environmental management practices. In addition to the correlation, internal marketing has an effect on environmental management.
Keywords: Environmental Management; Internal Marketing; Civil Aviation; Domestic Airlines